Women pioneers of science - Haber, Louis (New York : Harcourt Brace Jovanovich, 1979)
Biographies of 12 women pioneers and leaders in a variety of scientific fields.
Includes index.
Keywords: Women scientists -- Biography -- Juvenile literature; Women in science -- Juvenile literature; Scientists; Women -- Biography